1987
DOI: 10.1038/325811a0
|View full text |Cite
|
Sign up to set email alerts
|

Single stretch-activated ion channels in vascular endothelial cells as mechanotransducers?

Abstract: Endothelial cells line the inner surface of blood vessels and act as the main barrier to the passage of cells and large molecules from the blood stream to the tissues. Recent interest in the part played by the endothelium in regulating vascular tone has focused on the synthesis and secretion of prostacyclin and an endothelium-derived relaxing factor. Endothelial cells respond to blood-borne agonist, but how the endothelium senses and responds to mechanical forces generated by the flow of blood under pressure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
245
1
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(259 citation statements)
references
References 20 publications
11
245
1
2
Order By: Relevance
“…Since the reversal potential is near OmV in normal solutions ( Figure 3a), it appears that the channel displays poor selectivity for cations and thus Ca may permeate. A similar, presumably small permeability for Ca via nonspecific cation channels activated by stretch (Lansman et al, 1987) and thrombin or bradykinin Johns et al, 1987) has been recently reported in other cultured endothelial cells. On the other hand, the blocking action of internal Na for outward currents (Figure 3a) suggests that these channels display properties closer to those of other K-selective channels.…”
Section: Discussionmentioning
confidence: 95%
“…Since the reversal potential is near OmV in normal solutions ( Figure 3a), it appears that the channel displays poor selectivity for cations and thus Ca may permeate. A similar, presumably small permeability for Ca via nonspecific cation channels activated by stretch (Lansman et al, 1987) and thrombin or bradykinin Johns et al, 1987) has been recently reported in other cultured endothelial cells. On the other hand, the blocking action of internal Na for outward currents (Figure 3a) suggests that these channels display properties closer to those of other K-selective channels.…”
Section: Discussionmentioning
confidence: 95%
“…Of interest, ␤ 1 -integrins are associated with caveolae within which caveolin and signaling complexes regulate the activity of endothelial NO synthase (15,25,35,38). Direct or indirect activation of ion channel activity has also been implicated as an endothelial mechanosensor (1,3,8,16,18,19,43). Taken together, myriad signaling pathways could account for the observed DVR endothelial response to luminal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…With coronary perfusion pressures below 100 cm H 2 O, coronary vessels become maximally dilated and flow becomes pressure dependent 7 ; that is, autoregulation of coronary blood flow is lost 7 and control resides mainly in the endothelium of the vascular bed. An increase in coronary perfusion pressure results in an increase in water and cation content of endothelial cells, 2 which leads to stretch of endothelial cells and an elevation in coronary flow. 2 Vasodilators have little effect at the low perfusion pressure, but augment flow in the region of autoregulation in the isolated perfused heart, 8 including that of spontaneously hypertensive rats (SHR).…”
mentioning
confidence: 99%
“…An increase in coronary perfusion pressure results in an increase in water and cation content of endothelial cells, 2 which leads to stretch of endothelial cells and an elevation in coronary flow. 2 Vasodilators have little effect at the low perfusion pressure, but augment flow in the region of autoregulation in the isolated perfused heart, 8 including that of spontaneously hypertensive rats (SHR). "…”
mentioning
confidence: 99%